Coping With Imaginative Resistance. (19th April 2022) - Altshuler, Daniel; Maier, Emar
Abstract: We propose to characterize imaginative resistance as the failure or unwillingness of the reader to take a fictional description of a deviant reality at face value. The goal of the paper is to explore how readers deal with such a breakdown of the default Face Value interpretation strategy. We posit two distinct interpretative 'coping' strategies which help the reader engage with the resistance-inducing fiction by attributing the offending content to one of the fictional characters. We present novel empirical evidence that shows that actual readers use these strategies and we flesh out the exact workings of these strategies by integrating them into a general formal semantic framework for interpreting fiction.